Child Labour and Schooling of Children in Rural Bangladesh: A Multinomial Logit Model on Determinants. - Sarker, Md. Shahidul Islam; Md Mofackharul Islam (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper seeks better understanding the determinants of child labour and schooling of rural children in Bangladesh. Although literature identified the foremost factors of child labour which constrain schooling attainment of children, however literature has not clarified which determinants encourage children to combine school and work during their study period or solely work without schooling and how the effects of factors vary according to the gender of children as well. The present study contributes to fulfilling these gaps by studying the rural children of Bangladesh. Results show that some particular factors significantly affect to increase to combined (school and work) or work only outcomes and the effect size (size of odds) varies according to the gender of children. There is no significant factor which has a larger effect on the work only outcome for females compared to males.